Beyond profit: How ESG performance influences company value across industries? - Dwimayanti, Ni Made Desy; Sukartha, Putu Dyan Yaniartha; Putri, I Gusti Ayu Made Asri Dwija; Sisdyani, Eka Ardhani (University of Islam Malang, 2023)
Evaluating Environmental, Social, and Governance (ESG) scores is essential for understanding a company's long-term sustainability and value. These scores serve as a barometer of a firm's commitment to ethical, environmental, and social practices—attributes that are increasingly valued by both investors and consumers. However, despite their importance, previous studies have been constrained by their focus on smaller sample sizes and exclusive attention to the financial sector. Our study addresses this gap by delivering a comprehensive analysis of the impact of ESG scores on the valuation of companies across diverse industries, while purposefully excluding the financial sector, listed on the Indonesian Stock Exchange from 2019 to 2021. We analyzed 2,169 company-year observations, collected through non-probability purposive sampling, using multiple linear regression in STATA. Our findings reveal a robust correlation between ESG scores and company value, with firms boasting superior ESG scores consistently demonstrating enhanced size and profitability. These results emphasize that a genuine commitment to ESG principles not only elevates performance but also boosts attractiveness to investors, going beyond mere statutory compliance or superficial adoption.